Rescue of tau-induced synaptic transmission pathology by paclitaxel - Erez, Hdas; Shemesh, Or A.; Spira, Micha E. (Frontiers in Cellular Neuroscience, 2014)
Behavioral and electrophysiological studies of Alzheimer’s disease (AD) and other tauopathies have revealed that the onset of cognitive decline correlates better with synaptic dysfunctions than with hallmark pathologies such as extracellular amyloid-β plaques, intracellular hyperphosphorylated tau or neuronal loss. Recent experiments have also demonstrated that anti-cancer microtubule (MT)-stabilizing drugs can rescue tau-induced behavioral decline and hallmark neuron pathologies. Nevertheless, the mechanisms underlying tau-induced synaptic dysfunction as well as those involved in the rescue of cognitive decline by MTs-stabilizing drugs remain unclear. Here we began to study these mechanisms using the glutaminergic sensory-motoneuron synapse derived from Aplysia ganglia, electrophysiological methods, the expression of mutant-human tau (mt-htau) either pre or postsynaptically and the antimitotic drug paclitaxel. Expression of mt-htau in the presynaptic neurons led to reduced excitatory postsynaptic potential (EPSP) amplitude generated by rested synapses within 3 days of mt-htau expression, and to deeper levels of homosynaptic depression. mt-htau-induced synaptic weakening correlated with reduced releasable presynaptic vesicle pools as revealed by the induction of asynchronous neurotransmitter release by hypertonic sucrose solution. Paclitaxel totally rescued tau-induced synaptic weakening by maintaining the availability of the presynaptic vesicle stores. Postsynaptic expression of mt-htau did not impair the above described synaptic-transmission parameters for up to 5 days. Along with earlier confocal microscope observations from our laboratory, these findings suggest that tau-induced synaptic dysfunction is the outcome of impaired axoplasmic transport and the ensuing reduction in the releasable presynaptic vesicle stores rather than the direct effects of mt-htau or paclitaxel on the synaptic release mechanisms.